The Microbiota of Recreational Freshwaters and the Implications for Environmental and Public Health - Lee, Chang Soo; Kim, Minseok; Lee, Cheonghoon; Yu, Zhongtang; Lee, Jiyoung (Frontiers in Microbiology, 2016)
The microbial communities in recreational freshwaters play important roles in both environmental and public health perspectives. In this study, the bacterial community structure and its associations with freshwater environments were investigated by analyzing the summertime microbiomes of three beach waters in Ohio (East Fork, Delaware, and Madison lakes) together with environmental and microbial water quality parameters. From the swimming season of 2009, 21 water samples were collected from the three freshwater beaches. From the samples, 110,000 quality-checked bacterial 16S rRNA gene sequences were obtained and analyzed, resulting in an observation of 4,500 bacterial operational taxonomic units (OTUs). The most abundant bacteria were Mycobacterium and Arthrobacter of the Actinobacteria (33.2%), Exiguobacterium and Paenisporosarcina of the Firmicutes (23.4%), Planktothrix and Synechococcus of the Cyanobacteria (20.8%), and Methylocystis and Polynucleobacter of the Proteobacteria (16.3%). Considerable spatial and temporal variations were observed in the bacterial community of Actinobacteria, Cyanobacteria, and Firmicutes, where the bacterial community structure was greatly influenced by hydrological and weather conditions. The most influential factors were 1) water inflow for Bacteroidia and Clostridia, 2) turbidity for Gammaproteobacteria, 3) precipitation for Bacilli, and 4) temperature and pH for Cyanobacteria. One noticeable microbial interaction in the bacterial community was a significant negative relationship between Cyanobacteria and Bacilli (P < 0.05). Concerning beach water quality, the level of the genetic markers for cyanobacterial toxin (mcyA) was linked to the abundance of Cyanobacteria. In addition, unique distributions of the genera Enterococcus, Staphylococcus, Streptococcus, Bacteroides, Clostridium, Finegoldia, Burkholderia, and Klebsiella, together with a high density of fecal indicator E. coli, were markedly observed in the sample from Madison Lake on July 13, suggesting a distinctly different source of bacterial loading into the lake, possibly fecal contamination. In conclusion, deep sequencing-based microbial community analysis can provide detailed profiles of bacterial communities and information on potential public health risks at freshwater beaches.